2016
DOI: 10.1016/j.snb.2016.02.070
|View full text |Cite
|
Sign up to set email alerts
|

Improved on-chip impedimetric immuno-detection of subpopulations of cells toward single-cell resolution

Abstract: International audienceImpedance spectroscopy has gained interest for the quantitative detection of specific cells mainly due to a label-free detection and their miniaturization capability required for integration on chip and development of point-of-care diagnostics. In this paper, we report the study of impedimetric microfluidic devices with improved sensitivity targeting the immuno-detection of cells. The sensitivity of our system was evaluated in terms of the capacity of the electrodes to trap monocytes by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…VACNTs have previously been used as IDEs for capacitors with VACNT heights ranging from 34 to 70 μm with a 20–35 μm gap between electrodes. Although such tall heights are not typically reported for electrochemical biosensors, our previous work with an oral cancer biomarker had a VACNT electrode height of about 75 μm and gap of 25 μm . Smaller gap width between tall VACNT electrodes may likely improve sensitivity, a relationship that has previously been shown with planar electrodes …”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…VACNTs have previously been used as IDEs for capacitors with VACNT heights ranging from 34 to 70 μm with a 20–35 μm gap between electrodes. Although such tall heights are not typically reported for electrochemical biosensors, our previous work with an oral cancer biomarker had a VACNT electrode height of about 75 μm and gap of 25 μm . Smaller gap width between tall VACNT electrodes may likely improve sensitivity, a relationship that has previously been shown with planar electrodes …”
Section: Introductionmentioning
confidence: 81%
“…Microfluidic IDE sensors have also been shown to be more sensitive than static IDE sensors. 25 The exposed Cr leads provide the means for electrical contact within the plane of the sensor substrate to allow a 3D printed microfluidic channel to be clamped over the sensor (see also Figure S5, Supporting Information). Although fluorescence showed better coverage using the microchannel ( Figure S6, Supporting Information), initial electrochemical tests with the microfluidic channel demonstrated little improvement over static F-SA and F-biotin binding.…”
Section: Functionalization Of F-sa and Binding Of F-biotinmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to this, in this review we describe LOC devices based on the impedimetric method, where polymers and biological receptors are present. Manczak et al reported an impedimetric microfluidic device for sensitive immune-detection of cells [129]. The sensitivity of the described method was estimated as the ability of the electrodes to trap monocytes by specific immune-reaction with CD14 antibody immobilized on the modified-electrode surface, resulting in a change in impedance The electrode had been modified with mixture of 11-mercaptoundecanoic acid (MUA), mercaptohexanol (MH) and a mixture of aqueous solutions of N-hydroxysuccinimide (NHS) and 1-ethyl-3-(3-dimethylaminopropyl-carbodiimide) (EDC).…”
Section: Application Of Polymeric Materials In Loc Devicesmentioning
confidence: 99%